2020
DOI: 10.4028/www.scientific.net/kem.867.109
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Nanocrystalline Cellulose (NCC) from Ramie Fiber by Hydrochloric Acid Hydrolysis

Abstract: The present study investigates the structural, crystallinity index, crystallite size, morphological, and the dimension of Nanocrystalline Cellulose (NCC) extracted from ramie fiber by hydrochloric acid-hydrolysis. NCC was chosen because it has high strength and modulus compared to other natural materials. Ramie fiber was chosen because it has high cellulose content and abundant in Indonesia. The other reason is ramie has a high crystallinity index compared to other natural fibers. The extraction process was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Other acids used for the purposes includes HCl, HBr, H 3 PO 4 , H 2 C 2 O 4 etc. [41][42][43][44][45][46][47]…”
Section: Hydrolysis Of Cellulose: Acidic Treatmentmentioning
confidence: 99%
“…Other acids used for the purposes includes HCl, HBr, H 3 PO 4 , H 2 C 2 O 4 etc. [41][42][43][44][45][46][47]…”
Section: Hydrolysis Of Cellulose: Acidic Treatmentmentioning
confidence: 99%
“…On the other hand, the particle size distribution depends on the degree of aggregation [63]. Dimas et al [64] reported that the average size of NCCs hydrolyzed with 6, 8, and 10 M HCl were 8334, 3024, and 2086 nm, respectively, as measured by PSA. It indicates that NCCs dropped as the concentration of hydrochloric acid increased.…”
Section: The Particle Size Of Nccsmentioning
confidence: 99%
“…The micro fibrillated structure of the CNCs is also highly reactive, multiscale, and organized hierarchically (Klemm et al, 2011;Tonoli et al, 2019). Cellulose nanocrystals (CNCs) have attracted a lot of attention due to their physical and chemical properties, renewable nature, sustainability and use in composite materials (Azizi Samir et al, 2005;Dimas et al, 2020). The extraction process of CNCs can be carried out using numerous methods such as acid hydrolysis, temp-mediated oxidation, mechanical disintegration and enzyme-assisted hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydrolysis method frequently uses sulfuric acid, which produces a simple and less reaction time than other strong acids. Additionally, CNCs extracted using this method also have a functionalized surface, excellent crystallinity and strong colloidal stability in water (Chakrabarty & Teramoto, 2018;Dimas et al, 2020). Cellulose nanocrystals are mostly extracted from rich natural cellulose materials such as wood, straw, bamboo pulp, coconut husk, rice husk, and sugarcane bagasse etc.…”
Section: Introductionmentioning
confidence: 99%